1997
DOI: 10.1093/oxfordjournals.aje.a009201
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors in the Etiology of Brain Tumors Potential Role of Nitrosamines, Fat, and Cholesterol

Abstract: Several possible risk factors for brain tumors have been suggested in the past, including N-nitroso compounds, but with the exception of ionizing radiation, none has been consistently confirmed. The present study was aimed at assessing the influence of nutritional factors, including N-nitroso compounds, in the etiology of brain tumors, specifically gliomas and meningiomas. One hundred and thirty-nine cases with confirmed brain tumors diagnosed between 1987 and 1991 in central Israel and 278 controls matched ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 40 publications
2
62
1
1
Order By: Relevance
“…Studies have shown that hyperinsulinaemia promotes carcinogenesis in both colon and breast cancer and that the mechanism could possibly involve activity of insulin growth factor I (IGFI; Stoll, 1999;Kim, 1998). Kaplan et al (1997) have noted an association between meningioma and intake of saturated fat, which was not found in astrocytoma patients. Gene expression of different insulin-like growth factors has been reported in meningioma (Lichtor et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that hyperinsulinaemia promotes carcinogenesis in both colon and breast cancer and that the mechanism could possibly involve activity of insulin growth factor I (IGFI; Stoll, 1999;Kim, 1998). Kaplan et al (1997) have noted an association between meningioma and intake of saturated fat, which was not found in astrocytoma patients. Gene expression of different insulin-like growth factors has been reported in meningioma (Lichtor et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiologic studies of diet and vitamin supplementation have provided mixed support for the hypothesis that dietary N-nitroso compounds, antioxidants, or speci c nutrients might in uence the risk of either childhood or adult brain tumors, as reviewed in a number of reports (Berleur and Cordier, 1995;PrestonMartin and Mack, 1996;Wrensch et al, 1993), including some published more recently Hu et al, 1999;Kaplan et al, 1997;Lee et al, 1997;Lubin et al, 2000;Tedeschi-Blok et al, 2001). In a review of the relationship between childhood cancer and cured meat in the diet, Blot et al (1999) observed that most studies found no statistically significant association between the mother's total consumption of cured meat during the index pregnancy and the risk for developing a brain tumor in the child, but more studies found positive rather than negative relationships.…”
Section: Diet and Vitaminsmentioning
confidence: 99%
“…Several studies suggest that differences in diet and lifestyle can have major effects on tumour incidence, prevalence, and natural history (Blowers et al, 1997;Kaplan et al, 1997;Hu et al, 1999). Dietary restriction (DR) has long been recognised as a natural therapy that improves health, promotes longevity, and significantly reduces both the incidence and growth of many tumour types (Rous, 1914;Tannenbaum, 1959;Weindruch and Walford, 1988;Birt et al, 1999;Kritchevsky, 1999b).…”
mentioning
confidence: 99%